Pendidikan Anti Korupsi Berdasarkan Doa Bapa Kami pada Matius 6:11-13 dan Implementasinya pada Pelajaran Pendidikan Agama Kristen - Serepina Yoshika Hasibuan (Sekolah Tinggi Teologi Anugrah Indonesia, 2023)
Corruption prevention needs to be done starting from education. Promoting anti-corruption education must be integrated into all subjects including Christian Religious Education in elementary school. This article aims to understand the meaning of the Our Father's prayer in three phrases namely